Public Goods and Externalities: Agri-environmental Policy Measures in the United Kingdom - Jones, James (OECD Publishing, 2015)
Agriculture is a provider of commodities such as food, feed, fibre and fuel and, it can also bring both positive and negative impacts on the environment such as biodiversity, water and soil quality. These environmental externalities from agricultural activities may also have characteristics of non-rivalry and non-excludability. When they have these characteristics, they can be defined as agri-environmental public goods. Agri-environmental public goods need not necessarily be desirable; that is, they may cause harm and can be defined as agri-environmental public bads. Public Goods and Externalities: Agri-environmental Policy Measures in the United Kingdom aims to improve our understanding of the best policy measures to provide agri-environmental public goods and reduce agri-environmental public bads, by looking at the experiences of the United Kingdom. This report provides information to contribute to policy design addressing the provision of agri-environmental public goods including the reduction of agri-environmental public bads. It is one of the five country case studies (Australia, Japan, Netherlands, United Kingdom, and United States), which provide inputs into the main OECD book, Public Goods, Externalities and Agri-environmental Policy Measures in Selected OECD Countries
Keywords: Agriculture and Food; United Kingdom